The Effect of Citric Acid Soaking Time on The Levels of Lead (Pb) in Lorjuk Meat (Solen sp.) - Saltsa Arinda Putri; Endang Dewi Masithah; Eka Saputra (Universitas Airlangga, 2023)
Lead (Pb) is one of the pollutants in the aquatic environment that is often questioned because it has toxic and dangerous properties for aquatic biota and indirect impacts on humans who consume it. Lorjuk (Solen sp.) is one of the aquatic biotas that can accumulate lead in its body because it is a filter feeder. The levels of lead accumulated in the body of lorjuk can be reduced by immersion using a chelating agent, such as citric acid because can bind metals thereby freeing food from metal contamination such as lead. This study aimed to determine the effect of different soaking times with citric acid on the levels of lead (Pb) and determine the optimal soaking time to reduce the levels of lead (Pb) in lorjuk meat. This study used a Completely Randomized Design (CRD) which consisted of three treatments for soaking lorjuk meat (1.5 hours; 3 hours and 4.5 hours). The results showed that the duration of immersion in citric acid affected the levels of lead (Pb) in lorjuk meat. The best treatment is soaking for 4,5 hours because it could reduce the levels of lead with a percentage decrease of 14,38%, organoleptic values on appearance parameter 6,07 (whole, specific meat color, bright and clean); odor 7,40 (very fresh) and texture 7,07 (elastic, solid and compact), moisture content 78,25%; protein content 8,67%; lipid content 0,65% and ash content 0,61%.